Pulmonary complications of COVID-19 in patients with diabetes - A.V. Garnytska; O.S. Orlyk (Civic Union "Communicable Diseases Intensive Care Association", 2023)
BACKGROUND. The coronavirus disease (COVID-19), caused by the SARS-CoV-2 coronavirus, continues to pose a serious threat to global health. One of the key characteristic of this disease is its ability to attack the respiratory system, which can lead to pneumonia, especially in severe cases. Patients with diabetes, who already have certain pulmonary risks due to their disease, become particularly vulnerable to these complications. OBJECTIVE. On the basis of data from literary sources, to investigate the most frequent variants of pulmonary complications of COVID-19 in patients with diabetes mellitus (DM). MATERIALS AND METHODS. Object: pulmonological complications, as a result of transferred COVID-19. Research method: a review of literary sources. RESULTS. Among the pulmonological complications of COVID-19 in DM, most often in our practice we can encounter: pneumonia, acute respiratory distress syndrome, pulmonary fibrosis and inflammation of pulmonary vessels with the possible development of thrombosis. CONCLUSIONS. Glycemic control is a key factor to ensure optimal treatment of patients with diabetes with pulmonary complications of COVID-19, for timely correction of the regimen of hypoglycemic therapy. Medical treatment for pulmonary complications may include corticosteroids and anti-inflammatory drugs such as dexamethasone, especially in severe cases. However, it is important to take into account the ability of these drugs to increase glycemia, and accordingly choose treatment taking into account this factor, without excluding the possibility of prescribing insulin therapy. At the stage of recovery, an important role in the treatment of pulmonary complications of COVID-19 in patients with DM is played by a rational diet, physical activity and monitoring of the main indicators.